Brutalisierung der Jugendgewalt - gefühlte oder reale Zunahme von Straftaten?: eine Untersuchung anhand von Makrodaten amtlicher Statistiken und einer Kohortenstudie junger männlicher Insassen im Jugendstrafvollzug Baden-Württemberg - Schaffer, Bernadette (Tübinger Schriften und Materialien zur Kriminologie, 2022)
Time and again, violent acts committed by young people become the focus of public attention. In this context, special attention is often paid to the allegedly increased brutality of the offenses. In contrast, there are findings that point to a decline of juvenile delinquency and juvenile violence; also, there is no evidence of an increase in the quality of the offenses. The fact that the number of serious acts of violence is not increasing seems to confirm these findings. Therefore, in the first part of this study the development of the quantity of youth violence and its criminal law assessment are analysed. This analysis is carried out on the basis of data from official statistics, namely the police crime statistic, the criminal prosecution statistic and the prison statistic. The evaluation of the statistics offers a first approach to answering the question of an increased quantity and quality of violent offenses. With regard to registered youth violence, the differentiated analysis of various violent crimes shows a decrease or at most a constant level of violent offenses. Although there are indications that can also be interpreted to the contrary, the analysis overall supports the finding that the intensity of the acts of violence has not increased. However, these analyses do not allow final conclusions on the brutality of individual violent offenses since; there is a lack of further details of these criminal actions. Therefore, the focus of the dissertation is to close this gap by explicitly comparing the brutality of young people, the concrete use of violence during the act of violence, the more precise forms, the (accompanying) circumstances as well as the consequences for the victims. For this comparison, an analysis of two samples of court judgments from the years 1991/1992 and 2009/2010 was carried out with regard to juvenile detainees, who appeared in court because of at least one robbery offence. In summary, the results of both samples are remarkably consistent, which means that no significant difference between the samples in terms of the brutality of the violent offenses could be found.